PELATIHAN PENGOMPOSAN SAMPAH ORGANIK DENGAN SISTEM TAKAKURA PADA SISWA MA DARUL ULUM WARU - Muchammad Tamyiz; Laily Noer Hamidah; Ardhana Rahmayanti; Listin Fitrianah; Atik Widiyanti; Lily Octavia; Luqman Hakim (Journal of Science and Social Development, 2018)
The existence of waste in the environment, especially household waste needs to be addressed by waste management using a simple method, namely waste sorting. The training in this community service aims to: (1) Increase the knowledge of the community of Kedung Sumur Village regarding household waste management. (2) Empowering the community in sorting household waste. The target audience of PPM activities is Mr. and Housewives in Kedungsumur Village as many as 35 people. The PPM activity method uses the lecture method and question and answer discussion. The steps of PPM activities are lectures to explain the concept of the environment, classification of waste, types of organic waste, types of inorganic waste, examples of sorted waste bins. To measure the level of understanding, questionnaire analysis was carried out by the participants. Overall service activities can be said to be good and successful, seen from the success of the target number of trainees (> 100%), the activeness of participants in discussion sessions (> 50%), and the ability of participants in mastering the material seen from the results of the questionnaire, where > 80% participants successfully answered correctly > 5 questions for each category of questions.